Overcoming Speaking Skill Challenges in Vocational Students: A Practical and Interactive Approach - Tharisa Aura Maharani (English Education Study Program Faculty of Teacher Training and Education, 2025)
This research examines the challenges vocational students encounter in developing English speaking skills, focusing on psychological factors like anxiety and low self-esteem, as well as linguistic limitations such as inadequate vocabulary and grammar. Conducted as a qualitative descriptive study with 16 vocational high school students in Batam, the research employed observations, interviews, and self-assessment tools to explore student’s experiences and preferred teaching methods. Thematic analysis identified recurring issues, including anxiety and strong preference for interactive, peer-based learning environments. Findings suggest that practical, learner-centered approaches, such as problem-based learning, group discussions, and digital tools like video-based exercises effectively enhance speaking performance by reducing anxiety and improving fluency. These methods create supportive environments that boost confidence and motivation, which are essential for skill development in vocational contexts. The researcher highlights the need for innovative, engaging teaching strategies to address psychological and linguistic barries in English speaking. Future research should investigate the long-term impact of these approaches across various vocational settings and explore how digital resources might further reduce psychological barriers in language learning.